2016
DOI: 10.5194/acp-16-3289-2016
|View full text |Cite
|
Sign up to set email alerts
|

AIRUSE-LIFE+: a harmonized PM speciation and source apportionment in five southern European cities

Abstract: Abstract. The AIRUSE-LIFE+ project aims at characterizing similarities and heterogeneities in particulate matter (PM) sources and contributions in urban areas from southern Europe. Once the main PMx sources are identified, AIRUSE aims at developing and testing the efficiency of specific and non-specific measures to improve urban air quality. This article reports the results of the source apportionment of PM10 and PM2.5 conducted at three urban background sites (Barcelona, Florence and Milan, BCN-UB, FI-UB and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
140
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 300 publications
(190 citation statements)
references
References 50 publications
21
140
2
3
Order By: Relevance
“…PMF analysis performed on the datasets of all five studied cities, reported in Amato et al (2016), has shown that a distinct African dust factor is not easily obtained. Only in the case of Florence was a separate PMF factor profile for African dust identified, providing a potential reference value for this city and insight into the chemical profile of transported African dust.…”
Section: Sensitivity Analysis On the Estimation Of Net African Dustmentioning
confidence: 96%
See 3 more Smart Citations
“…PMF analysis performed on the datasets of all five studied cities, reported in Amato et al (2016), has shown that a distinct African dust factor is not easily obtained. Only in the case of Florence was a separate PMF factor profile for African dust identified, providing a potential reference value for this city and insight into the chemical profile of transported African dust.…”
Section: Sensitivity Analysis On the Estimation Of Net African Dustmentioning
confidence: 96%
“…The measurement periods, monitoring sites and number of valid chemical speciation samples for each city are presented in Table 1 (Diapouli et al, 2017). Details about sites, sampling and analytical procedures are provided in detail in Amato et al (2016).…”
Section: Sampling and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…(Tables 1 and 2) rather than being wind entrained soil particles. However, the midday peak in the diurnal pattern was not consistent with traffic alone and the crustal elements in its composition indicated that it was a mix of abrasion particles from vehicles and soil dust characterized by Al, Si, Ca, and Fe (e.g., Viana et al, 2008;Amato et al, 2016). A strong inverse correlation of the Road Dust factor with relative humidity and a higher contribution in drier months (e.g.…”
Section: Road Dustmentioning
confidence: 99%